Study of uranium bioaccumulation capacity of Salvia officinalis L. and Ocimum basilicum L. enhanced by citric acid - Ibragić, Saida; Smječanin, Narcisa; Hodžić, Sara; Ramčić, Šadija; Nuhanović, Mizra (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2020)
Plants possess various intrinsic mechanisms necessary to accumulate and either sequester or detoxify soil contaminants, including radionuclides. The aim of this study was to determine the bioconcentration factor of two fast growing plants Salvia offlicinalis L. (sage) and Ocimum basillicum L. (basil) that were cultivated in pH neutral soils artificially contaminated with three different concentrations of uranium (211, 352 and 470 mg/kg). The efficiency of citric acid was evaluated with respect to the enhancement of the phytoextraction process. The results showed that the bioconcentration factor did not differ significantly between the selected species (0.01 - 0.03). Citric acid was added in doses (50 mL, 30 mM) until the first effects of uranium phytotoxicity appeared. After four doses of citric acid, the bioconcentration factor reached 0.05 for both plants. The increase of uranium content taken up by the respective plants was more pronounced. Thus, the uranium content of sage grown in contaminated soil (470 mg/kg) increased from 6.03 to 21.28 mg/kg in citric acid-treated soil. The data obtained confirmed the efficiency of citric acid in enhancing phytoextraction of uranium and further suggest that even plants of a rather small biomass can be useful in phytoremediation given the appropriate treatment through induced phytoextraction with appropriate chemical agents.